How Fast Can a Human Run? − Bipedal vs. Quadrupedal Running - Kinugasa, Ryuta; Usami, Yoshiyuki (Frontiers in Bioengineering and Biotechnology, 2016)
Usain Bolt holds the current world record in the 100-m run, with a running time of 9.58 s, and has been described as the best human sprinter in history. However, this raises questions concerning the maximum human running speed, such as “Can the world’s fastest men become faster still?” The correct answer is likely “Yes”. We plotted the historical world records for bipedal and quadrupedal 100-m sprint times according to competition year. These historical records were plotted by using several curve-fitting procedures. We found that the projected speeds intersected in 2048, when for the first time, the winning quadrupedal 100-m sprint time could be lower, at 9.276 s, than the winning bipedal time of 9.383 s. Video analysis revealed that in quadrupedal running, humans employed a transverse gallop with a small angular excursion. These results suggest that in the future, the fastest human on the planet might be a quadrupedal runner at the 2048 Olympics. This may be achieved by shifting up to the rotary gallop and taking longer strides with wide sagittal trunk motion.